Evaluation of air pollutants in thermal-mineral springs: a case study of Agnano (Naples, Italy) and Contursi Terme (Salerno, Italy). Issue 1 (1st April 2022) - Pironti, C.; Ricciardi, M.; Motta, O.; Faggiano, A.; Miele, Y.; Fiorentino, A.; Cucciniello, R.; Proto, A.
Abstract: Thermo-mineral springs are widely spread over the volcanic areas of Naples and Salerno, two cities of southern Italy. Their use has been known by local inhabitants since they were one of the main curative therapies in the past. The variability of microclimate conditions, contaminations, air pollution and influence of visitors could be an important parameter for conservation of historical structure and to evaluate the damage of place, since atmospheric and gaseous pollutants could affect cultural heritage. The aim of this work was the determination of air concentration of H2 S, SO2, δ 13 CO2, chemical and microclimatic characterization of the thermal springs in Contursi Terme (Salerno, Italy) and Agnano (Naples, Italy), in order to assess their concentrations and potential effects on cultural heritage and human health.